MANAGEMENT DECISION-MAKING AND RISK MANAGEMENT IN THE DIGITAL ECONOMY - A. V. Kozlovsky; A. I. Mityushnikova (Вестник университета, 2020)
This article reviews the aspects of management decision-making in the digital economy and as a consequence the possibility of timely and qualitative response to emerging risks in the process of management decision-making. This issue is considered from the position of influence on management decision-making both internal and external factors of the operation of the company has been considered. Therefore, the topic under consideration is relevant, since the issue of digitalization with a large coverage extends in all areas and spheres of our life and as a result should cover more the possibility of improving the quality of management decision-making, but is it so?